PELAKSANAAN PENGAWASAN DINAS PERHUBUNGAN KOTA PEKANBARU DALAM MENGATASI KEMACETAN DI KOTA PEKANBARU TAHUN 2019 - Gusti Putra; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Congestion can affect various kinds of community activities because in addition to having an impact on the smooth running of community activities and no less important to the impact of community income. Pekanbaru is a city prone to traffic jams considering that Pekanbaru is the capital city of Riau Province. The problem of congestion in Pekanbaru City has not been maximally resolved due to indiscriminate parking, U-Turn, street vendors selling on the roadside, and public transportation that passes not in accordance with applicable regulations. The Department of Transportation as the agency in charge of overcoming congestion has tried to overcome congestion but has not been optimal. Based on these problems, the formulation of the research problem is "How is the Implementation of Supervision of the Pekanbaru City Transportation Service in Overcoming Congestion in Pekanbaru City in 2019?" This study aims to analyze and determine the supervision carried out by the Pekanbaru City Transportation Service in overcoming Congestion in Pekanbaru City in 2019. This research is a type of descriptive research using a qualitative approach. Data collection techniques in this study used interview, observation and documentation techniques, the data analysis used was qualitative analysis. The findings that can be concluded from the Implementation of Supervision of the Pekanbaru City Transportation Service in Overcoming Congestion in Pekanbaru City in 2019 are still classified as not optimal, even though 1) The government has supervisory standards in accordance with Regional Regulations and Perwako No. 2/2009 and 106/2016 concerning Traffic and Main Duties Pekanbaru City Transportation Agency; 2) the measurement system for monitoring is to carry out daily monitoring at locations prone to congestion and congestion prevention facilities and then reporting 3 times a month; 3) However, in measuring the implementation of supervision, it is still not optimal so that congestion still occurs; 4) as for the analysis of the causes of deviations from the standard of supervision, namely the lack of strictness of the Dishup in controlling illegal parking, public transportation (Angkot) not in accordance with the specified route, and the use of congestion prevention facilities by the community not being maximized; 5) Corrective actions taken by the government in the form of intensive monitoring in the future, additional human resources, budget, and supporting facilities for preventing congestion. Keywords: Determination, Measurement, Implementation, Comparison, and Correction